A moral na obra “o príncipe” de Nicolau Maquiavel - Ferreira Júnior, José (2023)
In Machiavelli's political philosophy, morals are seen as flexible and adaptable to the needs of the state, rather than a series of rigid and universal rules. The prince must be able to act according to the circumstances and needs of the moment. The purpose of politics is the well-being of the state, and the prince must be able to protect that well-being, even if it means sacrificing his morality. He argues that traditional virtues, such as honesty, justice, and clemency, can be counterproductive in political practice, and that the prince must be willing to sacrifice them in the name of the state's well-being. The research aims to analyze morality, taking as a starting point the work The Prince divided into blocks of chapters according to the theme they deal with: how to acquire a state?; secure society; arm the people; advice that must be observed by the ruler to maintain power; provision for choosing ministers; fortune, chance, God or free will?; and, serve the morals or interests of the State? When presenting the thoughts of the Florentine citizen, important reflections were made, identifying in the first two parts the morality employed by the thinker, as well as the attitudes that the prince/ruler must develop to acquire (first part) and ensure (second part) the state/ principality. In the third part, Machiavellian realism is discussed, emphasizing that the morality employed by the thinker is a practical action to ensure governability. In the penultimate part, the issue of fortune in Machiavellian philosophy will be discussed, exposed by the thinker in the last three chapters of the book, in which he argues that the ruler must prepare to take advantage of the opportunity presented to him. In the last chapter, it is debated whether the ruler should serve morality or the State.